2014
DOI: 10.1093/alcalc/agu076
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Vascular Calcification and Mortality among Alcoholics

Abstract: Vitamin D deficiency is common among alcoholic patients and is associated with low lean mass and liver dysfunction. Among non-cirrhotics, serum vitamin D levels below 30 ng/ml are associated with a greater long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…However, in our study, significantly increased cortical porosity was observed only in mice receiving ethanol which corresponds with a lower levels of ALP, GSH and Ca in the E group. Generally, liver dysfunction is associated with vitamin D deficiency [31]. Ethanolʼs toxic skeletal effects have been suggested to involve impaired vitamin D/calcium homeostasis [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, significantly increased cortical porosity was observed only in mice receiving ethanol which corresponds with a lower levels of ALP, GSH and Ca in the E group. Generally, liver dysfunction is associated with vitamin D deficiency [31]. Ethanolʼs toxic skeletal effects have been suggested to involve impaired vitamin D/calcium homeostasis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Substance use disorders increase the long term risk of serious health complications (Hossain et al, 2007;Nazrul Islam et al, 2001;Quintero-Platt et al, 2015) and are linked to increased mortality (Quintero-Platt et al, 2015). Liver disease, cirrhosis, cardiovascular disease (Quintero-Platt et al, 2015;Zhang et al, 2008), diabetes, pulmonary disease (Zhang et al, 2008), poor wound healing (Guo and Dipietro, 2010), lowered immune function (Housova et al, 2005;Quintero-Platt et al, 2015) and depression (Tolliver and Anton, 2015) have all been linked to substance use disorders, as have the spread of HIV and hepatitis through illegal drug use (Nabipour et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, less calcium will be absorbed when there is a lack of vitamin D. Heavy vitamin D nutrient deficiencies result in bone deformation, known as rickets (for an overview: [41]). Chronic alcohol consumption is associated with low vitamin D concentrations in the blood and a cause of low calcium admission responsible for bone changes [14,[42][43][44]. Moreover, vitamin D deficiency is common among alcoholic patients and results a higher long-term mortality [44].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol consumption is associated with low vitamin D concentrations in the blood and a cause of low calcium admission responsible for bone changes [14,[42][43][44]. Moreover, vitamin D deficiency is common among alcoholic patients and results a higher long-term mortality [44].…”
Section: Discussionmentioning
confidence: 99%